Integron Digestive Carriage in Human and Cattle: A “One Health” Cultivation-Independent Approach - Chainier, Delphine; Barraud, Olivier; Masson, Geoffrey; Couve-Deacon, Elodie; François, Bruno; Couquet, Claude-Yves; Ploy, Marie-Cécile (Frontiers in Microbiology, 2017)
Objectives: Dissemination of antimicrobial resistance (AMR) is a global issue that requires the adoption of a “One-Health” approach promoting integration of human and animal health. Besides culture-dependent techniques frequently used for AMR surveillance, cultivation-independent methods can give additional insights into the diversity and reservoir of AMR genetic determinants. Integrons are molecular markers that can provide overall and reliable estimation of AMR dissemination. In this study, considering the “One-Health” approach, we have analyzed the integron digestive carriage from stools of humans and cattle living in a same area and exposed to different antibiotic selection pressures. Methods: Three collections of human (general population (GP) and intensive care unit patients (ICU)) and bovine (BOV) stool samples were analyzed. The three main classes of integrons were detected using a multiplex qPCR both from total DNA extracted from stools, and from Gram-negative bacteria obtained by culture after an enrichment step. Results: With the cultivation-independent approach, integron carriage was 43.8%, 52.7% and 65.6% for GP, ICU and BOV respectively, percentages being at least 2-fold higher to those obtained with the cultivation-dependent approach. Class 1 integrons were the most prevalent; class 2 integrons seemed more associated to cattle than to humans; no class 3 integron was detected. The integron carriage was not significantly different between GP and ICU populations according to the antibiotic consumption, whatever the approach. Conclusions: The cultivation-independent approach constitutes a complementary exploratory method to investigate the integron digestive carriage of humans and bovines, notably within subjects under antibiotic treatment. The high frequency of carriage of integrons in the gut is of clinical significance, integrons being able to easily acquire and exchange resistant genes under antibiotic selective pressure and so leading to the dissemination of resistant bacteria.